Alkaline phosphatase triggered ratiometric fluorescence immunoassay for detection of zearalenone. (April 2023) - Wu, Shixiang; Zhang, Xingping; Chen, Wang; Zhang, Guohao; Zhang, Qian; Yang, Hualin; Zhou, Yu
Abstract: Inspired by the super-binding capacity of pyrophosphate (ppi) and copper ion (Cu 2+ ), an alkaline phosphatase (ALP) triggered ratiometric fluorescence immunoassay was established for detection of zearalenone (ZEN). In the assay, ALP-antibody acted as a bridge connecting ZEN concentration and ratiometric fluorescence signals. Due to the super-binding ability of ppi and Cu 2+, Cu 2+ was immobilized to form ppi-Cu 2+ complex and lost its oxidation activity. The presence of ALP can hydrolyze ppi and release Cu 2+ which can oxidize OPD to DAP. Since the excitation wavelength of DAP coincided with the emission wavelength of 2-aminoterephthalic acid (PTA-NH2 ), a ratiometric fluorescence immunoassay can be developed. The limit of detection (LOD) was 0.014 ng/mL and the linear detection range was 3.51–17.78 ng/mL. The ratiometric fluorescence immunoassay had high accuracy and reliability (recoveries, 101.10–107.20%; coefficient of variation (CV), 2.15–7.65%). This method provided new ideas for efficient and accurate detection of ZEN. Highlights: A ppi/Cu 2+ /OPD/PTA-NH2 -based ratiometric fluorescence immunoassay for zearalenone was developed. In comparison with other immunnoassays, this immunnoassay shows better sensitivity. There was no need to prepare any nanomaterials in advance.